2014
DOI: 10.1590/0001-3765201420130019
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phenolics and Flavonoids Extraction Conditions and Antioxidant Activity of Roasted Yerba-Mate Leaves (Ilex paraguariensis A. St.-Hil., Aquifoliaceae) using Response Surface Methodology

Abstract: This study focused on maximizing the extraction of total phenolics and flavonoids as well as the antioxidant activity measured by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay from roasted yerba mate (Ilex paraguariensis) as a function of time (5, 7.5 and 10 min) and temperature of extraction (60, 75 and 90°C). The data were subjected to Response Surface Methodology and the results showed that polynomial equations were significant, did not present lack of fit, and presented adjusted determination coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
5
32
0
2
Order By: Relevance
“…If both results are in agreement (relative standard error below 10%), then the regression model can be regarded as significant and predictive (Granato et al 2014b). Similarly to what was observed in the current study, Bassani et al (2014) Experimental data were subjected to RSM modeling and authors were able to identify the factors (alone and in combination) that affected the extraction of bioactive compounds and presented regression equations based on RSM to explain the results. Using linear regression analysis, it was possible to analyze the correlation between the antioxidant activity toward DPPH radical and the total phenolic content (Figure 2a), flavonoids (Figure 2b), and total anthocyanins (Figure 2c).…”
Section: Bioactive Compounds and Rsm Modelingsupporting
confidence: 64%
See 1 more Smart Citation
“…If both results are in agreement (relative standard error below 10%), then the regression model can be regarded as significant and predictive (Granato et al 2014b). Similarly to what was observed in the current study, Bassani et al (2014) Experimental data were subjected to RSM modeling and authors were able to identify the factors (alone and in combination) that affected the extraction of bioactive compounds and presented regression equations based on RSM to explain the results. Using linear regression analysis, it was possible to analyze the correlation between the antioxidant activity toward DPPH radical and the total phenolic content (Figure 2a), flavonoids (Figure 2b), and total anthocyanins (Figure 2c).…”
Section: Bioactive Compounds and Rsm Modelingsupporting
confidence: 64%
“…For the total flavonoids content, the effect of temperature (t-value = 3.758, p = 0.009) and the linear interaction between time and temperature (t-value = 6.846, p < 0.001) were the parameters that influenced the response, while the effect of time (t-value = 1.409, p = 0.208) was not important. This model also presented a high coefficient of determination (R 2 = 0.916 and adjusted R 2 = 0.895), implying that more than 90% of data variability was explained by the multiple linear regression model (Bassani et al 2014 The higher the extraction time (t-value = 1.972, p = 0.096) and, more importantly the temperature (t-value = 3.333, p = 0.016), the higher the content of total phenolic compounds. The interaction between these two factors also influenced positively the extraction of phenolic compounds from purple basil (t-value = 2.344, p = 0.057).…”
Section: Bioactive Compounds and Rsm Modelingmentioning
confidence: 94%
“…Berté et al (2011) reported a much lower DPPH scavenging activity for an aqueous spray-dried extract of yerba mate from Brazil (EC 50 value 2520 µg/mL) than the one determined herein. Bassani, Nunes & Granato (2014) attested that the total content of phenolic compounds was strongly correlated with the free radical scavenging activity towards DPPH radicals. Likewise, Anesini et al (2012) showed that chlorogenic and caffeic acids as well as the flavonoid rutin present in aqueous extracts of I. paraguariensis samples contributed directly to the antioxidant activity detected, by preventing lipid peroxidation.…”
Section: Bioactivity Of the I Paraguariensis Extractsmentioning
confidence: 96%
“…[16][17][18] Além disso, por se tratar de um derivado glicosilado, é natural que a rutina seja mais facilmente extraída em temperaturas elevadas. 19 Contudo, também é sabido que o emprego de altas temperaturas pode levar à degradação desse composto, 20,21 o que torna necessário o desenvolvimento de novas metodologias de otimização do método extrativo a fim de selecionar as melhores condições de extração, sem que a substância seja degradada durante o processo extrativo.…”
Section: Resultsunclassified